Creativity in the digital era: a comparison between human and AI evaluation in graphic design processes - Molares Cardoso, Julinda (2025)
Purpose. This study investigates whether evaluation using artificial intelligence (AI) with a customized GPT model can be comparable to, or complementary to, human evaluation in graphic design projects created by master's degree students. Methodology. A total of 180 logos were evaluated over six years using a 10-item Likert scale rubric. Each project received a double assessment, one by human experts and one by AI. Results and Conclusions. The results show agreement in five categories between human evaluators and AI (e.g., originality, relevance) while, in another five categories (e.g., balance, design principles), AI tended to overvalue the works when compared to human assessment. The qualitative analysis of the AI’s feedback identified strengths, but also limitations. In conclusion, a hybrid human-AI evaluation could improve fairness and efficiency in creativity grading, although AI alone fails to capture all subjective nuances. Original Contributions. This paper provides novel empirical evidence on the capabilities and limitations of AI (GPT) as a graphic design evaluator when compared to human assessment. It proposes a hybrid evaluation model that combines the sensitivity and expert judgment of the human evaluator, with the consistency and speed of AI, providing an innovative way to increase objectivity without losing subjective nuances in creativity evaluation.